واقع المحاسبة عن الأدوات المالية وفقاً للنظام المحاسبي المالي الجزائري (scf)ومعيار الإبلاغ المالي التاسع Ifrs 09 –التوافق وقابلية التحديث - سعيد, نورالدين; عز الدين, فؤاد (جامعة الوادي - University of Eloued, 2024)
This study aims to identify the reality of accounting for Algerian financial instruments compared to IFRS 09, in order to determine the compatibility of the financial accounting system (SCF) and international financial reporting standards with regard to accounting for financial instruments, as well as the requirements of modernization to keep pace with developments in the international arena, where the theoretical side dealt with a comprehensive presentation of accounting for financial instruments in accordance with both (SCF) and (IFRS9), and in order to reach the objectives of the research, this study was supported by a theoretical aspect, In which a questionnaire was relied on to process and analyze data using SPSS V22 software, the study concluded that the accounting of financial instruments is incompatible with (SCF) and the requirements of (IFRS9), which must be constantly updated to comply with the requirements of International Financial Reporting Standards.
The reality of accounting for financial instruments according to the Algerian financial accounting system and IFRS 09 -compatibility and upgradability
مقال
Keywords: الأدوات المالية ; محاسبة الأدوات المالية ; النظام المحاسبي المالي ; معايير الإبلاغ المالي الدولية; Financial Instruments; Accounting For Financial Instruments; Financial Accounting System; International Financial Reporting Standard.